Electrochemical Properties of Quinone-Based Organic Electrodes in LiCl/DMSO Electrolyte Solutions for Fluorine-Free Lithium Secondary Batteries - Sho OKUBO; Masahiko HAYASHI; Hiroaki TAGUCHI; Atsushi ARATAKE (Electrochemistry)
An organic electrolyte solution of 1.0 mol dm−3 LiCl/dimethyl sulfoxide (DMSO) was investigated for a fluorine-free battery with an electrode using 2,5-dimethoxy-1,4-benzoquinone (DMBQ) as the n-type active material and styrene butadiene rubber (SBR) as the binder. The DMBQ electrodes showed the initial discharge capacities of 222 mAh g−1 and 164 mAh g−1 for the DMSO solution of the LiCl system and the LiPF6 system, respectively. Moreover, they showed similar working voltages of 2.6–2.7 V, even though their plateau slopes had slight differences. In addition, the chemical bonding and crystallinity changes of DMBQ were confirmed during discharge-charge, suggesting that it reacted electrochemically with Li+ in the LiCl/DMSO solution. The results of cycle properties suggested that a gradual decrease in the discharge capacities would result from denaturation and dissolution of DMBQ during the redox process in the electrolyte solution.